Criminal Regulation Against Counterfeiting of Goods and Trademarks in the Industrial Sector - Mahmuctarom, Mahmuctarom; Irawan, Dimas Hendro; Pratama, Ilham Bayu Aji (Research Horizon, 2024)
Counterfeiting of goods and trademarks has become a serious threat affecting various industrial sectors around the world. In Indonesia, criminal law regulation related to counterfeiting of goods and trademarks has been adequate with relatively severe sanctions, but its effectiveness is moderate due to weak human resources, limited technology, and lack of coordination between law enforcement agencies. This research aims to examine the criminal regulation of trademark counterfeiting in the context of criminal law, with a focus on cases of product counterfeiting. The research method used is a qualitative method through a literature study to interpret various aspects related to the complexity of legal regulations, challenges in law enforcement, social and economic impacts, and prevention efforts made. The results show that diverse legal regulations at the national and international levels affect the effectiveness of law enforcement against trademark counterfeiting. Prevention efforts such as the development of new detection technologies and increased public awareness show positive steps in addressing this issue. This makes it necessary to harmonize legal regulations, strengthen human resources and technology, improve coordination between agencies, and increase public education so as to strengthen the protection of intellectual property rights in society.